STEVEN JOHNSON SYNDROME DENGAN IMPLIKASI ORAL PARAH SERTA PENATALAKSANAANNYA : LAPORAN KASUS - Fika Faradillah Drakel; Tenny Setiani Dewi (Denta Journal Kedokteran Gigi, 2022)
Background: Steven Johnson Syndrome (SJS) is an acute mucocutaneous syndrome that predominantly involve the skin and mucous membranes. SJS is an immune-mediated disease that have been associated with erythema multiforme (EM). The most common triggers are viruses, food allergies, autoimmune reactions and medicine. The medicines that most commonly cause SJS are non-steroidal anti-inflammatory drugs, antibiotics, antifungals, and anticonvulsants. Case: A 32-year-old man was consulted from the Dermatology Department with a diagnosis of drug induce SJS and was given cetirizine and dexamethasone. The patient presented to the Oral Medicine Department complaining of mouth pain, dysphagia, ulcers, oedema and haemorrhagic of the lips, difficult eating, drinking and speaking. Extra-oral examination found that the surface of the lips was covered with a white layer, bloody and crusted, and erythematous rash on his neck, arm, abdomen, palms and feet, with a diameter of 2-6 mm. Intra-oral examination found multiple ulcers and erosive lesions that spread on the tongue, palate, buccal and labial mucosa. This condition established as an oral lesion related to SJS. Case Management: The management of the oral lesion was given corticosteroid mouthwash, 0.12% chlorhexidine digluconate, lip compress with 0.9% NaCl and 1% hydrocortisone ointment. Conclusion: Steroid mouthwash to suppress inflammation as well as a combination of 0.12% chlorhexidine digluconate antiseptic drug suppresses the infection process and complications that continue in the oral cavity and 0.9% NaCl solution as a moist wound healing. This therapy plays an important role in the healing process of oral lesions in patients with SJS.